"Hot background" of the mobile inelastic neutron scattering system for soil carbon analysis. (January 2016) - Kavetskiy, Aleksandr; Yakubova, Galina; Prior, Stephen A.; Torbert, H. Allen
Abstract: The problem of gamma spectrum peak identification arises when conducting soil carbon analysis using the inelastic neutron scattering (INS) system. Some spectral peaks could be associated with radioisotopes appearing due to neutron activation of both the measurement system and soil samples. The investigation of "hot background" gamma spectra from the construction materials, whole measurement system, and soil samples over time showed that activation of 28 Al isotope can contribute noticeable additions to the soil neutron stimulated gamma spectra. Highlights: Neutron activated "hot background" of Al, Fe, Si, SiO2, NG MP320 was investigated. Activated isotopes and γ-peaks were identified. Activated isotopes in soil and MINS construction materials were listed. Contribution of hot background should be accounted in soil carbon analysis.